PHYSICAL ACITIVITY AND SYMPTOMS OF MENTAL DISORDERS IN BOSNIAN WOMEN - Šejla Šerifović Šivert,; Amra Nožinović Mujanović,; Hasnija Nurković, (Sport Scientific And Practical Aspects, 2025)
Although physical activity is often an indicator of positive mental state, reasonsfor exercising are numerous. Depending on the motivation, intensity and other factors, physical activity can have both positive and negative influence on women's mental health. The goal of this study was to find out if women in Bosnia and Herzegovina are physically active and to what extent, and to determine if there is a significant relationship between physical activity and symptoms of depression and body dissatisfaction. A sample included 215 female participants from Tuzla Canton. The following scales were used: Stankard body rating figure scale for body dissatisfaction, Beck's depression inventory and demographic scale which was designed for this study. Contrary to our expectations, there was no significant corelation between physical activity and symptoms of depression nor body dissatisfaction. Results were discussed in the context of current research about physical activity as a factor of mental health.